Evidence for several dipolar quasi-invariants in liquid crystals - Bonin, Claudio Julio (2013)
In a closed quantum system of N dipole coupled spins with magnetic quantum number I, there are (2I +1)N constants of motion, however, the possibility of observing such quasi-invariants (QIs) in solid-like spin systems in Nuclear Magnetic Resonance (NMR) is not a strictly exact prediction. The aim of this work is to provide experimental evidence of several QIs, in the proton NMR of small spin clusters, besides those already known Zeeman, and dipolar orders (strong and weak). We explore the spin states prepared with the Jeener-Broekaert pulse sequence by analyzing the timedomain signals yielded by this sequence as a function of the preparation times, in a variety of dipolar networks, solids and liquid crystals. We observe that the signals can be explained with two dipolar QIs only within a range of short preparation times. At longer times liquid crystal signals show an echo-like behaviour. We study their multiple quantum coherence content on a basis orthogonal to the z-basis and see that such states involve a signiﬁcant number of correlated spins. Then we show that the NMR signals within the whole preparation time-scale can only be reconstructed by assuming the occurrence of multiple QIs which we experimentally isolate.